Remembering Biblical Figures in the Late Persian and Early Hellenistic Periods: Social Memory and Imagination. Edited by Diana V. Edelman and Ehud Ben Zvi - Williamson, H. G. M. (The journal of theological studies, 2014)
Social memory has been a prominent feature of historical studies for several decades now, and, judging by the spate of books that have appeared in the last few years which try to relate it to various aspects of Old Testament study, it looks as though biblical scholars are just now catching up with a field which in other respects is beginning to look rather tired. Some specialists have sought to distinguish between social, cultural, and communicative memory, but the various terms are not used in a fully consistent manner by different writers, and, in any case, the distinctions are not sufficiently robust to be of particular further help in biblical studies, where the data are so comparatively few and our external knowledge so limited.